2008
DOI: 10.1242/dev.022244
|View full text |Cite
|
Sign up to set email alerts
|

Temporal requirements of the fragile X mental retardation protein in the regulation of synaptic structure

Abstract: Fragile X syndrome (FraX), caused by the loss-of-function of one gene (FMR1), is the most common inherited form of both mental retardation and autism spectrum disorders. The FMR1 product (FMRP) is an mRNA-binding translation regulator that mediates activity-dependent control of synaptic structure and function. To develop any FraX intervention strategy, it is essential to define when and where FMRP loss causes the manifestation of synaptic defects, and whether the reintroduction of FMRP can restore normal synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 69 publications
8
137
0
Order By: Relevance
“…5 A and B). The data confirmed that neuron volume is increased in the mutant (13,36). Furthermore, we provide direct counting of synapses, which are also increased in the mutant (Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…5 A and B). The data confirmed that neuron volume is increased in the mutant (13,36). Furthermore, we provide direct counting of synapses, which are also increased in the mutant (Fig.…”
Section: Resultssupporting
confidence: 84%
“…5 A and C). As previously reported, expression of NCS-1 is reduced and the number of synapses is increased in the fly fmr1 mutant (13,20). However, simultaneous overexpression of NCS-1 and Ric8a suppresses the synaptic phenotypes of each genetic alteration and yields a normal number of synapses (19).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These reports have provided considerable insight into the mechanism that might underlie abnormal synapse development and dendritic spine morphology in FXS. In Drosophila, FMRP is essential for synapse formation and experience-dependent axonal pruning during development (Gatto and Broadie, 2008;Tessier and Broadie, 2008). Studies in Fmr1 KO mice have further revealed that FMRP regulates protein synthesis-dependent axon pruning, dendritic spine elimination, and actin-dependent stabilization of spines.…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%